Bangladesh Development Update 2017 - World Bank (World Bank, Dhaka, Bangladesh, 2017)
The Bangladesh economy is weathering persistent global uncertainties relatively well. Poverty reduction is expected to have continued. Growth remained resilient, aided recently by recovery in exports and private investments. Inflation has decelerated benefitting from soft international commodity prices and prudent macroeconomic management. The outlook for Bangladesh’s main export destinations is projected to improve, although downside risks remain elevated. More recently, falling export growth and decline in remittances are emerging near term concerns. According to our model, increased capital accumulation can contribute significantly to boosting growth, but alone cannot deliver a sustainable and accelerated growth path. More is needed, including closing the inter-sectoral productivity gap through increased resource mobility, easing the constraints on firm level productivity and increasing female labor force participation in the formal sectors. In addition, poor infrastructure, inadequate energy supply, and inefficient financial intermediation combined with high cost of doing business remain the key obstacles hindering the realization of Bangladesh’s vast economic potential.